Clean Energy: installed cost and operating efficiency of a 1 MW photovoltaic plant (Research, Society and Development, 2022)
The use of solar energy has been increasing its space in the energy matrix. Brazil has great potential for applications using photovoltaic energy, but this potential is not fully explored. Due to this, the work proposes a case study on the implementation of a photovoltaic plant in the Academic Unit of Cabo de Santo Agostinho, one of the branches of the Federal Rural University of Pernambuco. The characterization of the implantation area, bibliographic surveys about the object of study were carried out, field visits to obtain photographic records and mapping of the processes, and analysis of the plant's executive project were also performed. To calculate the solar energy potential for the region, SunData software and MS-Excel were used to process the data. It was possible to estimate a potential of 747,877.19 kW of energy, which expresses the feasibility of the plant in terms of economic, technical and legal factors, providing data to support the planning of the operation and maintenance of the electrical system in the area under study, aligned with the sustainability policy proposed by this academic unit.